Is Sustainability Performance Comparable? A Study of GRI Reports of Mining Organizations. (February 2017) - Boiral, Olivier; Henri, Jean-François
The objective of this study is to analyze the measurability and interfirm comparability of sustainability performance through the qualitative content analysis of 12 sustainability reports of mining firms using the Global Reporting Initiative (GRI) guidelines. The systematic comparison of information disclosed in 92 GRI indicators sheds light on the reasons underlying the impossibility of rigorously measuring and comparing the sustainability performance of firms from the same sector, which are supposed to be strictly following the same reporting guideline. These reasons include qualitative aspects of sustainability, lack of compliance with GRI protocols, indicator contingency, ambiguous or incomplete information, data heterogeneity, and report opacity. The study makes it possible to return to the very notion of sustainability, its meaning, and flexible application by organizations. The results are discussed from three different theoretical perspectives (functionalist, critical, and postmodern), each of which proposes possible and complementary explanations of the main findings.